2012
DOI: 10.5296/jse.v2i3.1892
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Malaysian ESL Students' Writing Problems on Conventions, Punctuation, and Language Use at Secondary School Level

Abstract: <p>This study aimed at investigating the challenges in three aspects of writing development process, namely conventions, punctuation, and language use (proper use of grammar) in secondary school level from students and teachers experiences. The data was collected from 30 ESL students as the student participants of this research, from the upper and lower secondary school, Form 1 to Form 5, and 10 teacher participants teaching English language for upper and lower secondary levels with different teaching ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 8 publications
1
56
0
Order By: Relevance
“…Ghabool, Edwina, and Kashef (2012) revealed that Malaysian ESL students have problems in writing, especially in language use (grammar) and punctuation. Students still need some constant monitoring and explanation from the teachers specifically in developing a good piece of writing.…”
Section: Error Correction Techniques In Writingmentioning
confidence: 99%
“…Ghabool, Edwina, and Kashef (2012) revealed that Malaysian ESL students have problems in writing, especially in language use (grammar) and punctuation. Students still need some constant monitoring and explanation from the teachers specifically in developing a good piece of writing.…”
Section: Error Correction Techniques In Writingmentioning
confidence: 99%
“…What is interesting is that the students perceived punctuation in the introduction and conclusion as a major obstacle for their ESL writing. Similarly, the study by Ghabool (2012) also found that writers considered punctuation as one of their obstacles in ESL writing.…”
Section: Research Questionmentioning
confidence: 90%
“…A study by Ghabool (2012) was done on 30 ESL students from upper and lower secondary in Malaysia to investigate on the problems that ESL writers face when they compose.…”
Section: Past Researchmentioning
confidence: 99%
“…One would like to think that the Questions technique developed by the authors is just such an intervention! ESL students" writing and the writing errors they make are well documented (Maros, Hua, & Salehuddin, 2007;Musa, Lie, & Azman, 2012;Ghabool, Mariadass, & Kashef, 2012;Al -Khasawneh, 2010). In an effort to minimize errors L2 writing instructors should always keep in mind strategy development as well as language skill development when working with students (Myles, 2002).…”
mentioning
confidence: 99%